E-Learning Competencies for Elementary School Teachers in Botolan, Zambales, Philippines - Datugan, Kimberly V.; Cabal, Esmen M. (Future Science / FSH-PH Publications, 2023)
Teachers' communication has been forced online due to the spread of COVID-19. Although technology advancement has made many things possible, the transition to online learning isn't simple. This descriptive study measured the level and challenges encountered in E-learning among one hundred fifty elementary school teachers. This study investigated the level and challenges of E-learning among 150 elementary school teachers. The research measured competencies such as individual media competence, critical media competence, and educational design competence using a survey questionnaire. The majority of respondents were female teachers in the adult stage, with teaching experience and educational qualifications. The teachers considered themselves competent in E-learning and disagreed with the presence of challenges. However, there was a significant difference in challenges based on the highest educational attainment. An online training program was proposed to enhance E-learning competencies, and collaboration with agencies and software companies was suggested for technical assistance. Adequate technical and peer support during E-learning implementation were recommended. School heads were advised to focus on professional development emphasizing technology integration, and teachers were encouraged to utilize visualization tools. Collaboration between school heads and teachers was emphasized for the proposed training program and strategies to address challenges.